Pengaruh FOMO (Fear of Missing Out) dan Perbandingan sosial terhadap Social Media Jealousy pada Pengguna Aktif Media Sosial dalam Hubungan Pacaran - Feyza Amaliya Mai Yahya; Siti Jaro’ah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
Digital transformation has positioned social media as a primary space for interpersonal relationships while generating new psychological vulnerabilities in romantic dynamics. Exposure to open, symbolic, and ambiguous social content fosters social media jealousy, a form of jealousy shaped by interpretations of a partner's digital activities. This study aims to examine the roles of Fear of Missing Out (FoMO) and social comparison in shaping digital jealousy among active social media users in dating relationships. Using a quantitative correlational design, 213 young adults were recruited via purposive sampling. Instruments included the FoMO scale, the Iowa–Netherlands Comparison Orientation Measure (INCOM), and a modified social media jealousy scale. Multiple linear regression analysis revealed that FoMO and social comparison simultaneously have a significant effect on social media jealousy (). Partially, FoMO contributes to online relational surveillance, while upward social comparison fosters insecurity and distorted relationship evaluations. These findings confirm that digital jealousy is a multidimensional psychological construct formed through the interaction of cognitive and emotional factors within the social media ecosystem.